Accurate nanoparticle size determination using electrical mobility measurements in the step and scan modes. Issue 12 (1st November 2022) - Duelge, Kaleb; Mulholland, George; Zachariah, Michael; Hackley, Vincent A.
Abstract: A critical and extensive comparison was made between differential mobility analysis (DMA) measurements of the mean diameter of monodisperse gold nanoparticles (AuNPs), based on step-voltage mode and the more commonly used scan-voltage mode (commercially known as scanning mobility particle sizer, SMPS). Under specific conditions including a long scan time, the difference between mean diameters measured by the two modes of operation was less than the expanded combined uncertainty (95% confidence interval) for the step-voltage mode. In addition, a comparison was made between two different calibration methods for DMA: the use of a certified nanoparticle size standard (artifact) versus a direct measurement of the sheath flow rate. Important variables and limitations for accurate measurements by the scan-voltage method were identified and evaluated. The mean size shifts to smaller electrical mobility diameters as the scan time is reduced and the scan mode is unable to measure sufficient points across the peak of very narrow size distributions, leading to systematic errors. The use of a calibration particle corrects for the flow and DMA column geometric effects and was found to minimize the effect of a reduced scan time. A methodology is presented for the use of these AuNPs and other monodisperse calibration particles for accurately calibrating SMPS instruments for the measurement of the electrical mobility diameter distribution. Copyright © 2022 American Association for Aerosol Research Graphical Abstract: UF0001